The Seasonal Variations of Algae in Korpinar Pond (Elazig/Turkey) - Sonmez, Feray (Medwell Online, 2011)
Samples of algae living in Korpinar pond were collected from September 2008 to August 2009 and examined. Sampling was performed monthly. Some physical and chemical characteristics of the pond were measured throughout the duration of the study. The high chlorophyll a value and widespread presence of some macroscopic aqueous plants in the pond suggested that the concerned pond had a eutrophic character. Of the 60 taxa identified during the study, 42 were found to belong to Bacillariophyta division, 9 to Chlorophyta, 6 to Cyanophyta, 2 to Dinophyta and 1 to Euglenophyta division. The seasonal variations in these algae were examined together with their physical and chemical characteristics and the results of this examination were compared with the results of previous studies carried out in ponds.
Keywords: Korpinar pond; algae; epilithon; epipelon; plankton; seasonal variation; Elazig